2013
DOI: 10.1590/s1415-790x2013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation among pregnant women: results from a population-based survey study

Abstract: Objectives: To measure the prevalence and risk factors associated with iron supplementation among pregnant women in the municipality of Rio Grande, Southern Brazil. Methods: All mothers living in this municipality who had children in 2007 were surveyed for demographic, socioeconomic and health care received during pregnancy and childbirth. The statistical analysis consisted of Poisson regression with robust adjustment of variance, and the measure of effect was prevalence ratio (PR). Results: Among the 2,557 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
0
12
2
4
Order By: Relevance
“…Recently published data have shown that increased use of iron and reduced anemia are directly proportional to good quality antenatal care, with 6 or more visits starting early in the pregnancy [12,20]. However, in the current study, no relationship was seen between anemia rates and the number of antenatal care visits or the time of presentation (p>0.05).…”
Section: Discussioncontrasting
confidence: 83%
“…Recently published data have shown that increased use of iron and reduced anemia are directly proportional to good quality antenatal care, with 6 or more visits starting early in the pregnancy [12,20]. However, in the current study, no relationship was seen between anemia rates and the number of antenatal care visits or the time of presentation (p>0.05).…”
Section: Discussioncontrasting
confidence: 83%
“…13 In Senegal, it was found that 58% of pregnant women used 70% or more of iron supplements prescribed 25 and, in Vietnam, the mean duration of use of the supplement was 4.8 months. 23 The discrepancies observed between the prevalences of use of the iron supplement may be associated with various factors, such as greater use among populations with higher levels of schooling and income, [16][17][18][19][20][21] who have more extensive prenatal care coverage 13,15,18,19,22 and better access to the supplement. 18,21,23,25 However, the different ways of measuring the use of iron supplements in the studies may also contribute to the variations observed.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation of this is that the services investigated were giving more attention regarding the use of supplements to pregnant women who have historically been identified as more vulnerable. 22 The association between multiparity and lower use of iron supplements is widely documented in the literature. 14,15,22 Pregnant women who have already been through one or more pregnancies may be less concerned about health in gestation, especially if they have experienced a pregnancy without complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations